Digital Preservation and Mitigation of Cultural Heritage: Case Studies on Sekaran Sites in the Context of Toll Road Development - Cuikitalia, Cuikitalia (Knowledge Garden: International Journal of Library Studies, 2024)
Digital preservation is an important process to maintain the authenticity of cultural heritage sites that are threatened by infrastructure development. Many cultural heritage sites have just been discovered recently and preservation is required to preserve them. The rapid development of infrastructure can threaten the existence of cultural heritage sites in the area. The aim of this research is that digital preservation is an effective solution for maintaining the authenticity of cultural heritage sites and facilitating access to information in the future. In the context of agrarian law, there is a question about how the law views which is more important, the preservation of cultural heritage sites or the community's need for infrastructure. This study used a qualitative research method with a case study approach at the “Sekaran Site”, Lesanpuro which was affected by the construction of the Pakis toll road exit, Malang. Interviews were conducted with residents as well as analysis and documents available in the findings of the Sekaran cultural heritage site. The results of the study indicate that the use of digital technology and the development of digital platforms can assist in maintaining and communicating information about the Sekaran cultural heritage site. Digital preservation can also increase public awareness about the importance of preserving cultural heritage and can be an effective tool in overcoming the impact of infrastructure development on cultural heritage sites. In the case of the Sekaran Site, the Government is preserving the site by turning up to 17.5 meters from the starting point of the construction of the Malang Pandaan Toll Road. This was done after the discovery of piles of bricks arranged to resemble a building. In this case, digital preservation can assist in identifying threatened cultural heritage sites and facilitating the preservation process.